Echinoderms Community in Mokupa Beach Waters, Sub-district of Tombariri, Minahasa Regency - Andrea G Kambey; Unstain N. W. J. Rembet; Adnan S. Wantasen (Sam Ratulangi University, 2015)
Echinoderms community of intertidal zone in Tasik Ria beach, Mokupa village, Tombariri Sub-district, Minahasa Regency was studied to reveal its structure. Methods implemented to study the community were density, relative density, diversity, dominance and evenness focusing on echinoderms species. Those methods including species abundance and diversity introduced by Shannon-Wiener (‘H). Results from 10 species identified with total of 193 individuals were recorded in the study. In general, the result showed that the area still has good condition as a habitat for echinoderm communities. Keywords: Community, diversity, dominance A B S T R A K Komunitas Echinodermata di zona intertidal rataan terumbu di daerah Tasik Ria Desa Mokupa Kecamatan Tombariri, Kabupaten Minahasa, Provinsi Sulawesi Utara, dianalisis untuk memahami struktur komunitas organisme Echinodermata, menggunakan analisis tentang kepadatan, kepadatan relatif, keanekaragaman, dominasi, dan kemerataan spesies. Penelitian ini difokuskan pada kelimpahan dan keragaman spesies termasuk keragaman Shannon-Wiener spesies (H') masing-masing. Hasilnya mencatat 10 spesies dan total 193 individu. Secara umum, menunjukan daerah tersebut memiliki kondisi yang masih stabil sebagai tempat hidup komunitas echinodermata. Kata Kunci : Komunitas, keanekaragaman, dominasi 1Mahasiswa Program Studi MSP FPIK-UNSRAT 2Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi